Mortality trends and demographic-geographic disparities of autoimmune liver diseases among U.S. adults aged ≥45 years, 1999-2023 - Qiu, Chenjie; Shi, Honglei; Dai, Liangliang (Frontiers in Immunology, 2026)
ObjectiveTo analyze the temporal mortality trends and demographic/geographic disparities of autoimmune liver diseases (ALDs) among individuals aged 45 years or older in the U.S. from 1999 to 2023, and provide evidence for targeted prevention and control strategies.MethodsBased on the CDC WONDER database, multiple-cause-mention ALD-related deaths (AIH, PBC, PSC) were identified using ICD-10 codes. Age-adjusted mortality rates (AAMRs), annual percent changes (APC/AAPC) were calculated, and trend analyses were conducted via Joinpoint regression. The study population was restricted to decedents aged ≥45 years due to data availability constraints.ResultsTotal multiple-cause-mention ALD-related deaths increased by 165.05%, with AAMR rising from 1.65 to 2.74 per 100,000 (AAPC = 2.48). Females had a higher AAMR (2.97 per 100,000) than males (2.53 per 100,000) in 2023. The 45–54 age group had the fastest AAPC (2.56), and non-Hispanic Black individuals had the highest AAPC (2.94). The West had the highest AAMR (3.24 per 100,000) in 2023. Based on data from 1999-2020, in 2020, AAMR in nonmetropolitan areas (3.09 per 100,000) surpassed that in metropolitan areas, with widening urban-rural gaps.ConclusionU.S. ALD-related multiple-cause-mention mortality continues to rise among adults aged ≥45 years, with significant disparities across age, race/ethnicity, and urban-rural regions. Improving healthcare access for vulnerable populations and developing new therapies are essential to reduce the disease burden.